Fruit Chan's Made in Hong Kong - Cheung, Esther M. K. (New Hong Kong cinema., 2009)
This volume looks at Chan's tragic coming-of-age film which follows three disillusioned local youths struggling to navigate Hong Kong public housing projects and late adolescence amid violent crime, gang pressure, and broken homes.